Enhancing Academic Quality: Evaluation Practices in Higher Education - Tania Pretorius; Isaac Patsa (The Journal of Quality in Education)
The improvement of academic quality in higher education necessitates the implementation of innovative evaluation practices by lecturers. The emphasis on quality assurance in higher education emanated from globalisation and the aim of having common teaching standards that facilitate students' mobility within and across countries. Globalisation refers to an increasing but uneven integration of the world economy that reinforces a neoliberal logic (Sparke, 2013) and has been one of the driving forces that have allowed the expansion of higher education and the increasing relevance of quality assurance policy frameworks.